DEVELOPMENT AND IN VITRO EVALUATION OF PHYTOSOME OF TERBINAFINE HYDROCHLORIDE FOR ORAL DRUG DELIVERY - SHARMA, SHIVAM; VIVEK (International Journal of Applied Pharmaceutics, 2020)
Objective: The purpose of this study was to develop and in vitro evaluation phytosome of terbinafine HCL to enhance the bioavailability for oral route. Methods: The novel phytosome of terbinafine hydrochloride (TFH) was formulated with the molar ratio (1:2) of drug and phospholipid by using solvent evaporation technique. The resulting TFH-PC was determined by means of particle size analyzer (PSA), percentage yield, microscopy, drug content, transmission electron microscopy (TEM). Substantial contact of terbinafine HCL with phospholipids was completed through Fourier transforms infrared spectroscopy (FTIR). Results: The all relevant results of TFH-PC were showed that the percentage entrapment efficiency of formulation was found in 76% to 90%. In vitro release data were exhibited approximately 65% to 79% of the drug released from the TFH-PC formulation by using dialysis membrane technique. Therefore, Formulation (F3) was accomplished that phytosome contain the superior physical characters and compatibility with drug and phospholipids than to make it easy to overcome the competence of drug to pass the lipid-rich bio-membrane. Conclusion: In present work, terbinafine loaded phytosome was formulated for increasing the oral bioavailability of selected drug. Hence, TER-HCL phytosome were effectively improved the absorption of drug in form of phospholipids complex.